Sustainable siting process in large wind farms case study in Crete. (March 2015) - Tsoutsos, T.; Tsitoura, I.; Kokologos, D.; Kalaitzakis, K.
Abstract: The growing energy demand, as well as the European policy framework supporting the sustainable development, has strengthened the global interest in wind power installations during the last two decades. The interest is higher in areas with promising natural terrain, such as the Greek islands. The region of the island of Crete encourages the siting of wind farms due to the strong wind potential and the insular rough terrain. The aim of this research study is to develop and to implement a methodology of comprehensive evaluation and prioritization of areas for site selection of sustainable wind farms at a regional level, useful to support the strategic spatial planning of the island. The basic tool used to achieve the study's goals is the Specific Plan for Spatial Planning and Sustainable Development for Renewable Energy applied on Geographic Information Systems and the parallel integration of a systematic and flexible method of multicriteria analysis. The main output of this study is the provision of an objective and realistic overview of wind farm siting issue and the reinforcement of the regional and national policy/decision makers based on a sustainable regional development strategy avoiding fragmented decisions. Highlights: A methodological tool has been developed for the sustainable siting of wind farms. The critical energy issues of insular typology is presented. The carrying capacity of the natural systems in wind farms is calculated.